Predicting Incongruence between Self-reported and Documented Colorectal Cancer Screening in a Sample of African American Medicare Recipients. Issue 4 (1st October 2016) - Manning, Mark; Burnett, Janice; Chapman, Robert
Abstract : Assessments of colorectal cancer (CRC) screening rates typically rely on self-reported screening data, which are often incongruent with medical records. We used multilevel models to examine health-related, socio-demographic and psychological predictors of incongruent self-reports for CRC screening among Medicare-insured African Americans ( N = 3, 740). Results indicated that living alone decreased, and income increased, the odds of congruently self-reporting endoscopic CRC screening. Being male and having greater number of comorbidities decreased, and having less than a high school education increased, the odds of congruently self-reported fecal occult blood tests. Living alone, age and income had the most robust effects across classifications into one of four mutually exclusive categories defined by screening status (screened/unscreened) and congruence of self-reports. The results underscore the clinical importance of gathering socio-demographic data via patient interviews, and the relevance of these data for judging the veracity of self-reported CRC screenings behaviors.